Plasticisation effect on thermal and tensile properties of injection moulded short glass Fibreipol yamide 6,6 composites - Hassan, A.; Abdul rahman, N.M.M.; Yahya, R. (2010)

(untitled)
Polymer composites of polyamide 6,6 reinforced with short glass fibre were prepared by injection moulding. The composites under different conditions were investigated by thermogravimetric, differential scanning calorimetry, dynamic mechanical and tensile tests. The glass transition temperatures are found to be sensitive to moisture. According to the TGA results, the glass fibre loading in PA 6,6 does have increment effect on the thermal stability of the composites. In contrast, the incorporation of glass fibre and moisture into the PA 6,6 matrix result in a remarkable decrease in degree of crystallinity value. It is found that the incorporation of glass fibre into the polyamide 6,6 gives rise to a significant improvement in tensile modulus and tensile strength.However, fracture strain is reduced. Exposure to different environments from dry to wet conditions has result in a decrease in the strength and modulus for tensile mode, while tensile strain shows an increment from dry to wet conditions.